Hybridization patterns of Actinobacillus actinomycetemcomitans serotypes a-e detected with an rRNA gene probe - Saarela, M; Asikainen, S; Jousimies-Somer, H; Asikainen, T; von Troil-Lindén, B; Alaluusua, S (Oral microbiology and immunology, 1993)
This study reports a genetic characterization of Actinobacillus actinomycetemcomitans strains in relation to serotypes by using rRNA gene restriction patterns. Eighty-eight clinical strains were isolated from 20 unrelated subjects at one or several occasions. The strains were serotyped by using serotype-specific rabbit antisera against serotypes a, b, c, d or e. Three subjects harbored 2 A. actinomycetemcomitans serotypes, 15 subjects 1 serotype and 2 subjects untypable strains. Chromosomal DNA was digested with restriction endonuclease ClaI, BamHI, BglI or HindIII and hybridized to the rrnB ribosomal RNA operon of the Escherichia coli chromosome. Isolates belonging to the same serotype were genetically identical in the same individual but nonidentical if they belonged to different serotypes. Isolates of the same or different serotypes were genetically nonidentical in different individuals. The banding patterns of A. actinomycetemcomitans isolates recovered from the same individuals during several years always remained identical. The hybridization method using pKK3535 as a probe seemed suitable as an epidemiological tool for comparing the clonal identity of A. actinomycetemcomitans strains.